Children’s Garden Design: Young Children’s Perspectives on the Affordances of Outdoor Spaces - Beasley, Kimberley Dolina (Curtin University, 2015)
This qualitative case study of an early years setting sought young children’s perspectives on what is compelling in natural outdoor play spaces and on the affordances of the elements in the space. Five themes emerged from the interpretive analysis: creative affordances; active affordances; multisensory affordances; affordances for connoisseurship; and affordances for connections. The implications invite designers and educators to listen to children’s voices and to consider the affordances of the spaces from a child’s perspective.